A phase division-based multi-segment foot model for estimating dynamic foot arch stiffness during walking - Chenhao Liu; Jingang Yi; Long He; Yijun Zhang; Tao Liu (PLoS ONE, 2025)
The arch of the human foot plays a significant role in bearing weight and keeping gait balance. Previous studies mainly focus on the foot arch stiffness at the static or quasi-dynamic state of a particular foot shape. The variation of the linear arch stiffness across the entire walking gait has rarely been reported. This work presents a phase division-based multi-segment foot model that considers plantar aponeurosis’s tension force for calculating the dynamics of the medial longitudinal arch. Kinematics and ground reaction forces of 10 healthy young adults during walking are recorded and analyzed. The stiffness changes of the foot arch throughout the stance phase are calculated. The experimental results show that the foot arch experiences a stiff-compliant-stiff-compliant transition during a single stance phase, including an extremely low stiffness during the plantar contact phase. By comparing the foot arch stiffness results with those from previous studies, the accuracy of the proposed model is indirectly validated. This study presents a new approach to explore the variation of the linear stiffness of the foot arch across the entire stance phase during walking. The proposed multi-segment foot model provides a new method for solving foot dynamics that can be used for wearable sensing and assistive design and applications.